Gamified Interactive Quiz Innovation Fosters Behavioral Student Attention In Inclusive Schools: Inovasi Kuis Interaktif Tergamifikasi Menumbuhkan Perhatian Siswa Berperilaku Khusus Di Sekolah Inklusif - Rauhimidah, Siti; Nurhayati, Siti Rohmah (Indonesian Journal of Innovation Studies, 2026)
General Background Inclusive education strives to provide all learners equal access to meaningful academic opportunities within regular classroom settings. Specific Background Traditional teacher-centered instruction frequently fails to sustain the attention of students with behavioral disorders, causing classroom disruptions and diminished academic participation. Knowledge Gap Although digital tools offer motivational benefits, empirical evidence regarding the application of gamified platforms specifically tailored to accommodate the neuropsychological traits of special educational needs students in Indonesian inclusive elementary classrooms remains limited. Aims This study investigates how a gamification-based interactive quiz innovation accommodates learning needs, channels excess energy, and stimulates intrinsic motivation among fifth-grade students with behavioral disorders at Muara Wahau Elementary School. Results Utilizing a qualitative case study and classroom action research design, findings demonstrate that gamified interactive quizzes successfully shifted average learning interest from 42 percent to 88 percent across two cycles. Specifically, rule-based features minimized impulsive interruptions, visual dynamics sustained hyperactive focus, redirected digital competition reduced aggressive interpersonal tension, and instant reward systems stimulated inattentive students to participate actively. Novelty This research distinctly maps specific digital game mechanics directly to the remediation of distinct disruptive behavioral profiles within a regular educational setting. Implications Inclusive educators must integrate cooperative gamified platforms into regular instruction to seamlessly unite the learning needs of students with behavioral disorders and their regular peers into a supportive educational ecosystem. Highlights Wayground digital tools successfully shift academic participation averages from 42 percent to 88 percent across action cycles. Rule-based game mechanics directly minimize impulsive interruptions and redirect aggressive tension into structured competition. Cooperative digital play seamlessly unites regular peers with special needs children within a supportive ecosystem. Keywords Gamification; Interactive Quizzes; Learning Interest; Behavioral Disorders; Inclusive Education